Youth in Europe: Unemployment falling but major labor market problems persist - Karl Brenke (DIW Economic Bulletin, 2017)
In spring 2013, youth unemployment in the EU peaked and then declined sharply. Yet at least one in every six members of the economically active population between age 15 and 24 in the EU is still unemployed, and the unemployment rate among young persons is still 2.5 times higher than that of adults. The present study shows how young people's situation in the labor market has developed since 2013. The decline in unemployment was primarily caused both by a drop in the number of young people due to the demographic shift and their diminishing participation in economic life. The increase in employment played a less important role. Virtually all of the additional jobs were for a fixed time only, and the part-time employment rate continued on its upward trend. On average in Europe, the youth among the unemployed have a particularly high risk of unemployment, even with similar formal qualifications. In Central European countries, young people have a more advantageous situation in the labor market-probably as a result of practice-based vocational training. Since professional experience and references play key roles in improving people's prospects in the labor market, measures to improve young people's situation in the labor market should target the vocational training system.
Keywords: J21; J24; J60; 330; youth unemployment; youth guarantee; labor market developments